Optimization of lipase production by Aspergillus ibericus from oil cakes and its application in esterification reactions - Oliveira, Felisbela Maria Araújo (2017)
Due to the actual emphasis in revalorization of agro-industrial wastes and cost reduction of enzymes production, this work aimed the optimization of lipase production from different oil cakes (OCs) produced in Brazil, by solid-state fermentation using Aspergillus ibericus MUM 03.49 and the application of the produced lipase in hydrolysis and esterification reactions. Results presented showed higher lipase production using palm kernel oil cake (PKOC), yielding 127 ± 17 U/g. Through SSF optimization, using palm kernel oil cake (PKOC) mixed with sesame oil cake (SOC) in a ratio of 0.45 g/g PKOC per g total substrate at 57% moisture content, a production of 460 ± 38 U/g of lipase per mass of dry substrate was obtained after 6 days of fermentation. The obtained lipase was used in hydrolysis reactions, where it was observed higher production in short-chain triacylglycerols (TAGs) substrates. Also, it was applied in esterification reactions, where the formation of butyl decanoate using 5% (w/v) of biocatalyst was the most efficient. SSF of PKOC and SOC was a low cost competitive process to obtain A. ibericus lipase that can be used in aroma esters production, with application in the food industry.